Pengaruh Penerapan E-Filling Pada Kepatuhan WPOP Pegawai Negeri Sipil Dengan Pemahaman Internet Sebagai Variabel Pemoderasi - Putra Agniveda, I Gusti Ngurah Agung; Supadmi, Ni Luh (E-Jurnal Akuntansi, 2019)
This study aims to determine the effect of the application of e-filling on the compliance of the civil servant taxpayers with an understanding of the internet as a moderating variable in the East Denpasar Primary Tax Office. The number of samples used in this study were 100 respondents out of 16,732 effective civil servant populations in East Denpasar Primary Tax Office. The method of determining the sample used was non-probability sampling with a purposive sampling technique. Data collection in this study was conducted by questionnaire method. The data analysis technique used is the analysis of Moderated Regression Analysis (MRA). The results showed that the application of e-filling had a positive effect on the compliance of the civil servant taxpayers and understanding the internet was not able to moderate the effect of implementing e-filling on the compliance of the civil servant taxpayers at East Denpasar Primary Tax Office. Keywords: E-filling, understanding of the internet, taxpayers compliance.